Oscillatory Flow Bioreactor (OFB) applied in enzymatic hydrolysis at high solid loadings - Buchmaier, J. (Array, 2020)
Within this study, an enzymatic hydrolysis process using α-cellulosic feedstock was performed in a specially designed plug-flow reactor, referred to as an Oscillatory Flow Bioreactor (OFB). The aims of this approach were to achieve intensification in terms of realising a more energy- and resource-efficient enzymatic hydrolysis, as well as to set the basis for continuous processes in such a reactor. The OFB performance was evaluated for high solid loadings of up to 15 %, and compared to the performance of a Stirred Tank Reactor (STR). Experimental results of the OFB operating at an oscillation frequency of 2 Hz and an oscillation amplitude of 10 mm exhibit better conversion efficiencies (+ 6.7 %) than the STR after 24 h, while requiring only 7 % of the STR power density (W m–3). Therefore, the OFB enables efficient, uniform mixing at lower power densities than STRs for applications with high solid loadings.